2022
DOI: 10.30762/jeels.v4i1.330
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Writing Skill through Collaborative Writing Technique: From Theory to Practice

Abstract: Based on the school based curriculum states that the teaching of writing skill is aimed at enabling students to master the functional and monologue texts in the form of genres. However, previous studies revealed that Indonesian students still have problems in learning it because writing itself involves aspects of grammatical form, choice of words, generating and organizing the ideas into coherent and logically ordered. Those have become a hard challenge for many students in Indonesia. To overcome this, collabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…In addition, writing is one of four English abilities that students need to master. Writing is the language skill most individuals use least (Davies, 2002;Supiani, 2017). It is also a skill that is generally formally learned at college, and that many individuals do not handle well.…”
Section: The Concept Of Writingmentioning
confidence: 99%
“…In addition, writing is one of four English abilities that students need to master. Writing is the language skill most individuals use least (Davies, 2002;Supiani, 2017). It is also a skill that is generally formally learned at college, and that many individuals do not handle well.…”
Section: The Concept Of Writingmentioning
confidence: 99%
“…It remains, however, the responsibility of ESL teachers to guide and help the pupils to master writing skills, progressively. Supiani (2017) observes that writing skills should not be taught palely and teachers must think of ways to teach writing using different approaches.…”
Section: Writingmentioning
confidence: 99%
“…Studies in L2 contexts have also shown that during the process of collaborative writing, the learners focus not only on the grammatical accuracy and lexical choices, but also on discourse (Lin & Maarof, 2013;Meihami et al, 2013;Zhang, 2018). In L2 classroom, collaborative writing enables the learners to observe and model their peers' thinking and writing strategies (Supiani, 2017). During collaborative activities, the students are expected to have opportunities to brainstorm, initiate ideas, discuss them, and then start to write collaboratively.…”
Section: Introductionmentioning
confidence: 99%